204k views
3 votes
Can some one help me plz trying to figure out? Need help ASAP

Can some one help me plz trying to figure out? Need help ASAP-example-1

1 Answer

3 votes

Answer:


a. = -35 \\ b. = 9a + 1 \\ c. = -35

Explanation:


a. \\ = > \: 7a - 1 + 2a + 2 \\ \\ = > 7( - 4) - 1 + 2( - 4) + 2 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (a = - 4) \\ \\ = > - 28 - 1 - 8 + 2 \\ \\ = > - 37 + 2 \\ \\ = > - 35 \\ \\ \\ b. \\ = > 7a - 1 + 2a + 2 \\ \\ = > 7a + 2a - 1 + 2 \\ \\ = > 9a + 1 \\ \\ \\ c. \\ = > 9a + 1 \\ \\ = > 9( - 4) + 1 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (a = - 4) \\ \\ = > - 36 + 1 \\ \\ = > - 35

User Iffy
by
4.5k points